Pengembangan Media Pembelajaran Pengenalan Pahlawan Nasional Sulawesi Utara Berbasis Augmented Reality - Nadya Verona Viani Kamasi; Stephanie Mariane Felly Nangoy (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2023)
This research aims to develop a prototype of a learning media for the introduction of national heroes, specifically in the North Sulawesi Province, to help elementary school students gain a better understanding of national heroes, particularly in North Sulawesi. the study employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. the final outcome of this research is the creation of an augmented reality-Based hero introduction application for a subject with the theme "my heroes," in the form of an android application that can be used on smartphones. The black box testing resulted in a 100% unit testing feasibility percentage, interpreted as highly feasible. The expert media testing yielded an 88.88% feasibility percentage, interpreted as highly feasible. The material expert testing conducted by a teacher at SD Gmim Kakas, resulted in a 93.68% feasibility percentage, interpreted as highly feasible. Furthermore, the usability testing conducted by five students from SD Gmim Kakas resulted in a 92.13% feasibility percentage, interpreted as highly feasible.